Risk factors, clinico-epidemiological profile of tuberculosis among children attending a tertiary care hospital: a two year study - Tenali, Ravikumar; Badri, Naveen Kumar; Kandati, Jithendra; Ponugoti, Munilakshmi (International Journal of Contemporary Pediatrics, 2018)
Background: TB remains as the one among the top 10 causes of death worldwide. In 2016, 10.4 million people fell ill with TB, and 1.7 million died from the disease with 0.4 million with HIV. At least 1 million children become ill with TB each year. Children represent about 10-11% of all TB cases. Having knowledge of the risk factors for tuberculosis infection in children is important to evaluate the level of ongoing transmission of infection and to help adapt activities within national TB control programs. The main objective is to study the risk factors and their association and variable clinical features in cases of pulmonary and extra pulmonary tuberculosis. Methods: The main objective is to study the risk factors and their association and variable clinical features in cases of pulmonary and extra pulmonary tuberculosis. Results: 98 cases of TB were confirmed out of total 628 with a prevalence of 17.07% in the study with 78 PTB cases and 20 EPTB. Females were more with male to female ratio of 0.7:1.5-9 years was the most common age group in the study. Statistically significant association was found between old history of ATT, HIV positivity, contact with an open case of TB and malnutrition (p value<0.05). TB meningitis was the most common EPTB (10/20 cases) followed by tuberculous lymphadenitis (5/20). 69.39% (68/98 cases) were smear positive, radiologically 59.18% of cases were positive and Tuberculin skin test was positive in 46.94%. Conclusions: Childhood tuberculosis is a neglected entity in developing countries due to underreporting and difficulties in diagnosis due to variable clinical picture in children. Hence epidemiological surveillance studies in children are required to determine the actual prevalence of pulmonary and extra pulmonary cases of tuberculosis. Increased efforts are required to isolate TB bacilli from body fluids to identify early the childhood cases and manage them to prevent disease burden in the community.